2013
DOI: 10.1016/j.toxicon.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the localization of tetrodotoxin between wild pufferfish Takifugu rubripes juveniles and hatchery-reared juveniles with tetrodotoxin administration

Abstract: To reveal the accumulation profile of tetrodotoxin (TTX) in pufferfish Takifugu rubripes juveniles, we compared the localization of TTX in various tissues among wild juveniles and hatchery-reared juveniles with or without TTX administration using immunohistochemical technique with anti-TTX monoclonal antibody. Immuno-positive reaction was observed in hepatic tissue, basal cell of skin and olfactory, olfactory epithelium, optic nerve and brain (optic tectum, cerebellum, medulla oblongata) of wild juveniles (bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…However, most of TTX was detected in skin and muscle in case of juveniles (Fig.1). Okita et al [22] also detected TTX from hepatic tissue, basal cell of skin and olfactory, olfactory epithelium, optic nerve and brain in wild-caught T. rubripes juveniles (SL 4.7-9.4 cm), by immunohistochemical technique with anti-TTX monoclonal antibody. They also confirmed the same TTX localization in non-toxic artificially-raised juveniles after 5-days TTX administration with similar method of this study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, most of TTX was detected in skin and muscle in case of juveniles (Fig.1). Okita et al [22] also detected TTX from hepatic tissue, basal cell of skin and olfactory, olfactory epithelium, optic nerve and brain in wild-caught T. rubripes juveniles (SL 4.7-9.4 cm), by immunohistochemical technique with anti-TTX monoclonal antibody. They also confirmed the same TTX localization in non-toxic artificially-raised juveniles after 5-days TTX administration with similar method of this study.…”
Section: Discussionmentioning
confidence: 96%
“…Such non-toxic T. rubripes juveniles are attracted to TTX by olfactory [21] and accumulate TTX when they are fed TTX-containing diet [22]. Furthermore, TTX was detected not only in liver but also basal cell of skin both in the wild juveniles and artificially-raised juveniles to which TTX were orally administrated [22].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the popular assumption, TTX-bearing organisms use toxin for the defense against predators. Okita et al [66] showed that the survival rate of puffer fish ( T. rubripes ) fry grown under artificial conditions was significantly lower than the survival of fry from the natural environment. The authors explained the low survival rate of the cultured fry by nonadoptive behavior and low TTX concentration (below detectable level) in comparison with the fry from natural habitat.…”
Section: Ecology Of Marine Ttx-producing Bacteriamentioning
confidence: 99%
“…Recently, Sakakura et al (unpublished) found that when TTX was administered to hatchery-raised nontoxic juveniles, their ecologic behavior became similar to that of wild juveniles, making it more difficult for predators to prey on them. In addition, Okita et al (2013b) revealed that when TTX was orally administered to nontoxic T. rubripes juveniles, it passed through the blood-brain barrier to reach the brain, and that TTX was similarly localized in the brain in toxic wild juveniles. These findings suggest that TTX is involved in controlling information transmission in the central nervous system of pufferfish, and may strongly influence the physiology and ecology of pufferfish.…”
Section: -3 Other Functionsmentioning
confidence: 99%